Reading the Helicon Collage: Hidden Stories in the Collected Fragments - Domínguez Romero, Elena (Miscelánea: A Journal of English and American Studies, 2012)
The present study sets out to show that the pastoral anthology Englands Helicon can be read as a compilation of separate poems or fragments, or of fragments interspersed with sequences of poems that form love stories here and there throughout the anthology. For this to be possible, the Classic models of Virgil’s Eclogues II and VII have been followed so that the reconstruction of the sequence will be based on an analysis of the above mentioned models, taking the sequence as an imitatio cum variatione of the two eclogues. Both possibilities were equally valid for seventeenth century readers who knew the literary tradition of the time. It all depended on how they chose to approach the text. This study also contends that most contemporary readers —unless specialists in Early Modern Literature— would need to be given the appropriate tools in order to be able to organise the fragments into love stories, that is, to read the Helicon poems in sequence.
Keywords: Early Modern; Virgil; Anthologies; Reading Models; Sequences